Brain structural and functional connectivity and the progression of neuropathology in Alzheimer's disease - Matthews, P; Filippini, N; Douaud, G (2012)
In our contribution to this special issue focusing on advances in Alzheimer's disease (AD) research since the centennial, we will briefly review some of our own studies applying magnetic resonance imaging (MRI) measures of function and connectivity for characterization of genetic contributions to the neuropathology of AD and as candidate biomarkers. We review how functional MRI during both memory encoding and at rest is able to define APOE4 genotype-dependent physiological changes decades before potential development of AD and demonstrate changes distinct from those with healthy aging. More generally, imaging provides a powerful quantitative measure of phenotype for understanding associations arising from whole genome studies in AD. Structural connectivity measures derived from diffusion tensor MRI (DTI) methods offer additional markers of neuropathology arising from the secondary changes in axonal caliber and myelination that accompany decreased neuronal activity and neurodegeneration. We illustrate applications of DTI for more finely mapping neurodegenerative changes with AD in the thalamus in vivo and for defining neuropathological changes in the white matter itself. The latter efforts have highlighted how sensitivity to the neuropathology can be enhanced by using more specific DTI measures and interpreting them relative to knowledge of local white matter anatomy in the healthy brain. Together, our studies and related work are helping to establish the exciting potential of a new range of MRI methods as neuropathological measures and as biomarkers of disease progression. © 2013 The authors and IOS Press. All rights reserved.